Liver injury in sepsis: manifestations, mechanisms and emerging therapeutic strategies - Xinqi Xu; Tingyu Yang; Jiapan An; Bin Li; Bin Li; Zhimin Dou; Zhimin Dou (Frontiers in Immunology)
Sepsis is defined as a condition related to infection that manifests with multiorgan dysfunction, representing a life-threatening state. Consequently, severe complications frequently occur, with liver injury being one of the most prevalent serious complications of sepsis. Liver dysfunction during sepsis serves as an independent predictor of mortality. This review provides a comprehensive overview of current research on sepsis-induced liver injury (SILI), encompassing the clinical manifestations, diagnostic criteria, pathogenesis and therapeutic strategies associated with this condition. SILI may manifest as hypoxic hepatitis due to ischemia and shock, cholestasis resulting from abnormal bile metabolism, or bile duct sclerosis. The pathophysiology of sepsis involves intricate interactions among the inflammatory response, oxidative stress, and cell death. All of these factors complicate treatment and represent potential targets for therapeutic intervention. Furthermore, this review addresses the limitations inherent in conventional therapies currently employed for managing SILI and emphasizes the potential of novel targeted strategies aimed at addressing the fundamental mechanisms underlying this condition.